2016
DOI: 10.1111/dom.12794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on oral glucose tolerance in individuals with low vitamin D status and increased risk for developing type 2 diabetes (EVIDENCE): A double‐blind, randomized, placebo‐controlled clinical trial

Abstract: Weekly doses of vitamin D in individuals with suboptimal vitamin D levels who were at risk for type 2 diabetes did not improve oral glucose tolerance or markers of glycaemic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 38 publications
2
82
2
1
Order By: Relevance
“…They also demonstrated that administration of 1,25(OH) 2 D into the brain dramatically decreased the food intake and body weight in obese rodents. Although a clear cause and effect for vitamin D in glucose and insulin metabolism and body weight has been established, it is surprising that studies on vitamin D supplementation and CVD have yielded inconsistent results [41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that administration of 1,25(OH) 2 D into the brain dramatically decreased the food intake and body weight in obese rodents. Although a clear cause and effect for vitamin D in glucose and insulin metabolism and body weight has been established, it is surprising that studies on vitamin D supplementation and CVD have yielded inconsistent results [41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Although mixed, there is evidence linking elevated serum PTH and lower 25OHD to a variety of negative health outcomes in both men and women [43,44,45,46,47,48,49,50,51,52]. Some researchers hypothesize excess PTH secretion to be involved in the development of hypertension, a theory supported by data indicating a positive correlation between blood pressure and serum concentrations of PTH [53,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In several large community based cohort studies, low serum 25OHD levels have not shown to be associated with poor CVD outcomes [45,47]. The relationship of low serum 25OHD levels and insulin resistance and metabolic syndrome has been more consistently reported [48,49], although prospective studies do not always suggest improvements in insulin sensitivity with improvements in vitamin D status [50,51]. Whether or not the dosages used in these studies and effective in raising serum 25OHD levels is often debated.…”
Section: Discussionmentioning
confidence: 99%
“…A number of RCTs suggested that supplementation of vitamin D could improve insulin resistance and FPG (8)(9)(10)(11). However, certain studies obtained contrary results (12) or identified no beneficial effect (13)(14)(15)(16). Dutta et al revealed that vitamin D supplementation could significantly lower the progression of diabetes (17); while reports from others indicated that supplementation with vitamin D had no effect on T2DM prevention (13,18,19).…”
Section: Introductionmentioning
confidence: 99%